2015
DOI: 10.1523/jneurosci.3646-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of Different Pedunculopontine Targets in a Novel Rodent Model of Parkinsonism

Abstract: The pedunculopontine tegmental nucleus (PPTg) has been proposed as a target for deep brain stimulation (DBS) in parkinsonian patients, particularly for symptoms such as gait and postural difficulties refractory to dopaminergic treatments. Several patients have had electrodes implanted aimed at the PPTg, but outcomes have been disappointing, with little evidence that gait and posture are improved. The PPTg is a heterogeneous structure. Consequently, exact target sites in PPTg, possible DBS mechanisms, and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 80 publications
2
64
0
Order By: Relevance
“…A recent study on an animal model of PD showed that stimulation of the anterior PPN induced freezing and worsened gait, but gait was improved by posterior PPN stimulation [21]. …”
Section: Stereotactic Targetingmentioning
confidence: 99%
“…A recent study on an animal model of PD showed that stimulation of the anterior PPN induced freezing and worsened gait, but gait was improved by posterior PPN stimulation [21]. …”
Section: Stereotactic Targetingmentioning
confidence: 99%
“…In that respect, the influence of PPN DBS on cortical structures (and in fine on the cortico-striatal activity) is also to be considered (Gut and Winn 2015) just as an modulatory effect on BG and thalamus regarding the dense projection from the MRF to the thalamic nuclei (Paré et al 1988; Van der Werf et al 2002;Benarroch 2008;Galvan and Smith 2011) and the different components of the BG (Lavoie and Parent 1994b;Mena-Segovia et al 2004;Martinez-Gonzalez et al 2011;Dautan et al 2014).…”
Section: Implication For Dbsmentioning
confidence: 99%
“…Other workers have challenged the importance of the PPN as a component of the MLR since PPN lesions do not alter locomotor capability (Winn, 2006; Hernández-Chan et al, 2011; MacLaren et al, 2014; Gut and Winn, 2015, 2016). Moreover, neurons activated during locomotion (indicated by the presence of the activity-dependent marker Fos) are found in the CnF and other nearby areas, including the deep mesencephalic nucleus (DpMe; Jordan, 1998; Vianna et al, 2003; Heise and Mitrofanis, 2006), but not in the PPN.…”
Section: Introductionmentioning
confidence: 99%